Quality of Life Changes Evaluation on the Basis of the International Classification of Functioning at the Third Stage of Rehabilitation: a Retrospective Cohort Study of 40 Women with Breast Cancer - Galina E. Ivanova; Tatiana V. Builova; Lyudmila A. Belova; Yuri D. Udalov; Viktor V. Mashin; Andrey Yu. Suvorov; Anastasia A. Kuvaiskaya (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. The article reflects long-term and distant consequences of antitumor therapy, from three to six months from thebeginning of treatment, in patients with breast cancer. Analysis of the identified effects allowed to determine the structure of therehabilitation diagnosis based on the International Classification of Functioning.AIM. To designate the main International Classification of Functioning codes for breast cancer patients corresponding to the third stageof rehabilitation, to evaluate the effectiveness of rehabilitation measures at this stage of rehabilitation in breast cancer patients whoreceived different methods of treatment for this disease.MATERIAL AND METODS. The study was conducted on the basis Federal Research and Clinical Center of Radiology and Oncologyof the Federal Medical and Biological Agency of Russia for the period October-January 2021-2022, including the data analysis of 40patients (all women) with breast cancer stages I-IV, being at the third stage of rehabilitation 3-6 months after the complex antitumortreatment with the persistence of adverse events due to the therapy, the mean age of patients is 58 .6 ± 1.2 years.RESULTS AND DISCUSSION. The need for rehabilitation measures in patients with breast cancer persisted and increased after the endof antitumor treatment. A brief set of International Classification of Functioning was formed on the basis of complaints and evaluationof patients admitted to the third stage of medical rehabilitation from the standpoint of a biopsychosocial approach. Rehabilitationdiagnosis distinctive features were identified and, accordingly, the rehabilitation program was developed at the third stage of medicalrehabilitation of patients with breast cancer.CONCLUSION. The results of the study confirm the long-term effects of antitumor treatment, which suggests the need for rehabilitationmeasures to prevent the development and progression of complications and to improve the quality of life of breast cancer patients.